6_ r(x + 2) - 3 = s(x - 4)

rx + 2r - 3 = sx - 4s

rx - sx = 3 - 4s -2r

x(r - x) = 3 - 4s - 2r

Hence x = (3 - 4s - 2r) / (r - x)

7_ (x - y)/(w - z) = a

(x - y) = aw - az

(x - y - aw) = -az

HENCE z = - (x - y - aw)/a

8_ B = 2/3 a(r + s)

3/2 * B = a(r + s)

3B/a = r + s

3B/a - r = s

Hence s = (3B - ar)/a

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up